Brooding Technology Use and Technical Efficiency among Egg Producers in Oyo State, Nigeria - O. Idiaye, Chuks; F. Adebayo, Adebusola; B. Oluwatayo, Isaac (Talenta Publisher, 2022)
This paper investigated the types of brooding technology used by egg producers in Oyo State, Nigeria and its effect on technical efficiencies of the producers. The study was carried out in two Local Government Areas (LGAs) of Oyo State with data obtained from a total of 139 egg producers (farmers). Descriptive statistics was used to profile the farmers, probit model was employed to analyse the determinants of choice of brooding management technology, Cobb-Douglas stochastic frontier function was used to estimate technical efficiency among the farmers and Tobit regression model was also employed to ascertain technical efficiency determinants. The results show that only 9.4% of the farmers used modern brooding technology and over 50% of them employed unskilled labour. Sex of the farmer (p<0.10), household size (p<0.05) and having a secondary income (p<0.05) were the significant factors influencing adoption of modern brooding technology. Farmers who adopted the traditional brooding technology were found to be 4.3% more efficient than those using modern technology. Age (p<0.00), sex (p<0.05) and production experience (p<0.05) significantly affected their technical efficiencies. It was therefore recommended that technology subsidies, adequate extension training and skill acquisition be injected into the poultry industry to improve production efficiency. Â